Meningkatkan Hasil Belajar Melalui Pembelajaran Kooperatif Tipe STAD Pada Mata Pelajaran Kimia - Sri Murwatiningsih (Jurnal Dewantara, 2018)
As a result of the learning method has not been much involved chemical activity and cooperation among students, then the expected learning outcomes have not been able to achieve maximum completeness. Based on the analysis of class XII, acquired 67% of students who have achieved KKM. So there are still 33% of students who have not reached KKM. The research objective of this study was to determine the improvement of student learning outcomes through a strategy of cooperative learning type STAD in chemical. Research results through cooperative learning type STAD has been done has been the achievement of optimal learning is exhaustiveness Minimum Criteria (KKM), which has been set for the school subjects in class XI is 75 (for a scale of 0 - 100). Already reached 80% or more KKM (No remedial).